CPL-01, an Investigational Long-Acting Ropivacaine, Exhibits Extended-Release Properties after Mini-abdominoplasty. Issue 1 (2022) - Xu, Hanghang Tommy; Chen, Lee; Chen, PJ; Pan, Christine; Onel, Erol; Gottlieb, Ira J.
No abstract available